Proteomic and Isotopic Response of Desulfovibrio vulgaris to DsrC Perturbation - Leavitt, William D.; Venceslau, Sofia S.; Waldbauer, Jacob; Smith, Derek A.; Pereira, Inês A. Cardoso; Bradley, Alexander S. (Frontiers in Microbiology, 2019)
Dissimilatory sulfate reduction is a microbial energy metabolism that can produce sulfur isotopic fractionations over a large range in magnitude. Calibrating sulfur isotopic fractionation in laboratory experiments allows better interpretations of sulfur isotopes in modern sediments and ancient sedimentary rocks. The proteins involved in sulfate reduction are expressed in response to environmental conditions, and are collectively responsible for the net isotopic fractionation between sulfate and sulfide. We examined the role of DsrC, a key component of sulfate reduction, by comparing Desulfovibrio vulgaris DSM 644T to a mutant strain deficient in DsrC production. Both strains were cultivated in parallel chemostat reactors at identical doubling rates and sulfate reduction rates. Under these conditions, the wildtype produced a sulfur isotopic fractionation of 17.3 ± 0.5 ‰, while the mutant produced a fractionation of 12.6 ± 0.5 ‰. The enzymatic machinery that produced these different fractionations was revealed by quantitative proteomics. Results were consistent a cellular-level response that throttled the supply of electrons and sulfur supply through the sulfate reduction pathway – perhaps in response to limited DsrC availability. We conclude that the smaller fractionation observed in the mutant strain is a consequence of sulfate reduction that proceeded at a rate that consumed a greater proportion of its overall capacity for sulfate reduction. These observations have consequences for models and interpretation of sulfate reducer isotopic fractionation in both lab and natural settings.